Μ-Particle tracking velocimetry and computational fluid dynamics study of cell seeding within a 3D porous scaffold. (November 2017) - Marin, A. Campos; Grossi, T.; Bianchi, E.; Dubini, G.; Lacroix, D.
Abstract: Cell seeding of 3D scaffolds is a critical step in tissue engineering since the final tissue properties are related to the initial cell distribution and density within the scaffold unit. Perfusion systems can transport cells to the scaffold however; the fact that cells flow inside the scaffold pores does not guarantee cell deposition onto the scaffold substrate and cell attachment. The aim of this study was to investigate how fluid flow conditions modulate cell motion and deposition during perfusion. For such a purpose, a multiphase-based computational fluid dynamics (CFD) model was developed in conjunction with particle tracking velocimetry experiments (PTV) which for the first time were applied to observe cell seeding inside a 3D scaffold. CFD and PTV results showed the strong effect of gravity for lower flow rates leading to cell sedimentation and poor transport of cells to the scaffold. Higher flow rates help overcome the effect of gravity so more cells travelling inside the scaffold were found. Nonetheless, fluid flow drags cells along the fluid streamlines without intercepting the scaffold substrate. As a consequence, if cells do not deposit into the scaffold substrate, cell adhesion cannot occur. Therefore, cell-scaffold interception should be promoted and the present computational model which predicts the effect of gravity and fluid drag on cells trajectories could serve to optimise bioreactors and enhance cell seeding efficiency.